Microwave absorption performance and broadband absorption optimization of reduced graphene oxide - CHU Hairong; ZHOU Mengyu; SHI Shuangqiang; REN Sue (Cailiao gongcheng)
The microwave absorption performances of different contents and superimposed layers of large sheet reduced graphene oxide （rGO） absorbers have been studied， and the rGO is obtained from the thermal reduction of graphene oxide by the improved Hummers method. The calculated results indicate that the absorption performance is first enhanced and then weakened with the increased rGO content. When the mass fraction of rGO is 1.0% and the thickness is 2.2 mm， the effective absorption bandwidth （EAB，≤-10 dB） reaches 5.4 GHz （12.0-17.4 GHz）. When the mass fraction of rGO is 1.5% and the thickness is 1.8 mm， the EAB reaches 5.0 GHz （13.0-18.0 GHz）. Because the EAB of the single-layer rGO absorbing material is narrow， an improved genetic algorithm has been used to optimize the EAB of multi-layer superimposed rGO absorbing material， with the different content rGO absorbing material as the material library. The EAB of multi-layer rGO absorbing material is significantly improved after optimization. The 3-layer rGO absorbing material with a thickness of 3.94 mm exhibits the widest EAB of 11.5 GHz （6.5-18.0 GHz）. This study greatly improves the ultra-wide band absorption performance of graphene， which has important scientific significance and engineering value.